Pengaruh Estetika Visual dan Personal Branding Terhadap Social Currency Content Creator TikTok di Indonesia - Hendi Thamrin (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study examines the influence of visual aesthetics and personal branding on the and social currency of TikTok content creators in Indonesia. Utilizing a quantitative methodology, this research assesses the relationship between the visual quality of content and its ability to generate social currency, as well as the impact of these variables on personal branding development. The study sample consists of randomly selected TikTok content creators. Data were collected via online questionnaires and analyzed using regression techniques. The findings are expected to provide insights for content creators on strategies to enhance visual aesthetics to maximize the effects of social currency and strengthen personal branding on digital platforms.